PENGARUH PEKERJAAN ORANG TUA DAN KEYAKINAN DIRI TERHADAP MINAT BERWIRAUSAHA SISWA DI SMK NEGERI 10 SURABAYA - Setyowati, Dwi Indah (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aimed to determine the influences of parental employment and self-confidence of the students interest on entrepreneurship in 10th State Vocational School of Surabaya, academic year 2012-2013. Populations of this study were 582 students and 106 samples were selected by using purposive sampling. Data were collected by questionnaires. Analysis technique was using multiple linear regression analysis. Partial results of the study concluded that the work of the parents has no influence on the interest in entrepreneurship, while self confidence has an influence of the students interest in entrepreneurship. Simultaneously, this study concluded that parents work and self-confidence significantly influences students interest in entrepreneurship students in 10th State Vocational School of Surabaya.